2020
DOI: 10.6001/biologija.v65i4.4118
|View full text |Cite
|
Sign up to set email alerts
|

The influence of laser irradiation on the development of vegetative mycelium Pleurotus ostreatus

Abstract: The article presents the results of the study on the influence of laser irradiation on the development of vegetative mycelium and the period of the occurrence of the corcules of the fruit bodies of Pleurotus ostreatus. It has been established the growth processes of P. ostreatus, can be best stimulated by applying laser irradiation of mycelium with a green spectrum of light for 10 s. According to this mode of exposure, the best increase in the growth rate of mycelium of 38.3% and the appearance of the largest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Subsequently, using a sterile steel tube, 5 mm diameter mycelial disks were cut from the uterine culture. Before plating on the substrate, they were irradiated with LED lasers (Reshetnyk et al, 2019). Four types of irradiation were used in the study: the control culture grown without irradiation, while three others had a single exposure to laser light for 15 s (red, blue, and green spectrum).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, using a sterile steel tube, 5 mm diameter mycelial disks were cut from the uterine culture. Before plating on the substrate, they were irradiated with LED lasers (Reshetnyk et al, 2019). Four types of irradiation were used in the study: the control culture grown without irradiation, while three others had a single exposure to laser light for 15 s (red, blue, and green spectrum).…”
Section: Methodsmentioning
confidence: 99%
“…Irradiation of sowing mycelium of G. lucidum and L. edodes with both coherent and incoherent light of low intensity, where as a source of coherent visible light used modifications of gas lasers: helium-neon LGN-215 with radiation at a wavelength of 632.8 nm (red light ) and argon ion laser (modified model LGN-106M1) -radiation with a wavelength of 514.5 (green light) and 488.0 nm (blue light) caused an increase in polysaccharide synthesis and the amount of biomass [11]. In previous studies, we found that laser irradiation of vegetative mycelium of P. ostreatus with light of different spectral composition activates mycelial growth, so we hypothesized that the use of photoactivated mycelium will increase the synthesis of biologically active substances and the amount of biomass [6].…”
Section: Literary Reviewmentioning
confidence: 99%
“…It should be noted that the use of helium-neon and argon lasers, which have large dimensions and significant energy consumption, complicates the technology of stimulating the growth and development of fungi [5]. In our opin-ion, it is much more effective to use LED lasers to intensify the metabolic processes of macromycetes [6].…”
Section: Introductionmentioning
confidence: 99%